Current protocols in the management of oral submucous fibrosis: An update. (4th May 2017) - Arakeri, Gururaj; Rai, Kirthi Kumar; Boraks, George; Patil, Shekar Gowda; Aljabab, Abdulsalam S.; Merkx, M.A.W.; Carrozzo, Marco; Brennan, Peter A.
Abstract : Oral submucous fibrosis (OSMF) is a debilitating condition of oral cavity which has significant potential for malignant transformation. In spite of over 20 years of research, the pathogenesis of the condition is still obscure and no single management modality is effective. Many OSMF treatment protocols have been proposed to alleviate the signs and symptoms of the disorder and there is overwhelming evidence that as areca nut is primary cause, stopping its use may have a considerable effect on symptoms rather than reversing pre‐existing fibrosis. We present a review of the current protocols for managing OSMF.